Modernizzazione e potere locale: l’azione politica di Fiorentino Sullo in Irpinia. 1943-1958 - Pierluigi Totaro (Clio: Saggi di scienze storiche, archeologiche e storico-artistiche, 2012)
A long-serving leader of the Christian Democratic Party from mid-1940s to late 1950s, Fiorentino Sullo led an intense political action in the province of Avellino, combining exercise of power and political planning, programmatic appeals and rational distribution of resources, political and administrative management of State’s intervention in the public sphere and its bodies, efficient control and modernization of the territory. For over fifteen years, he intended to address and solve the typical dilemma faced by every modernizing elite and posed by the clash between the poles of conservation and transformation. His political career was characterized by a deep understanding of the traditional traits of the local communities, persistent and inevitable in the development of the relationship between politics and society. He also highlighted, in his activities, a strong orientation towards political change and the socio-economic development of a backward periphery.